Avaliação do desempenho cardíaco de ratos infartados e tratados com óleo de soja por via intramuscular - Lisbôa Júnior, Sérgio (2012)
After myocardial infarction, compensatory remodeling of cardiac chambers occurs secondary to left ventricular overload with reduction of myocardial contractility (Stefanon et al. 1994; Mill et al 2011). In a previous study we demonstrated that the treatment with soybean oil, 100 µl intramuscular for 15 days, increased cardiac performance without change blood pressure and it was associated with increased Na+ /K+ ATPase activity and SERCA2a protein expression (Ribeiro Junior et a., 2010). Since the decrease in myocardial contractility after myocardial infarction is associated with changes in expression of these enzymes, the purpose of this study was to evaluate whether treatment with soybean oil, intramuscularly for 15 days, can improve cardiac performance in rats subjected to acute myocardial infarction. Methods: Male Wistar rats (230–250 g) were used for this study. All rats had free access to water and were fed with rat chow ad libitum. The animals were divided into four groups: Sham Soybean group: animals underwent sham operation and were treated with soybean oil 0.1 mL for fifteen days. Sham group: animals underwent sham operation and were treated with 0.1 mL of 0.9% NaCl solution for fifteen days. Myocardial Infarction (MI) Soybean group: the left coronary artery was permanently occluded and the animals were treated with 0.1 mL intramuscular soybean oil for fifteen days; Myocardial Infarction group (MI): the left coronary artery was permanently occluded and the animals were treated with 0.1 mL of 0.9% NaCl solution for fifteen days. After 15 days of treatment animals were anesthetized and sacrificed to evaluate the ventricular pressure and myocardial mechanics. Values were analyzed using the t-test or ANOVA (one- or two-way). When ANOVA revealed a significant difference (p < 0.05), the Tukey or Bonferroni test was applied. Results: The myocardial infarction scar was not different between groups (MI Soybean: 34.13 9 ± 5 % N = 8; MI: 34.75 ± 6 % N = 8). The treatment with soybean oil did not change the left ventricular weigh. However, the infarcted group treated with soybean oil showed better cardiac performance compared to infarcted group treated with placebo, and this increase was accompanied by an increase in SBP (MI: 89.11 + 6.4 mmHg x MI Soybean: 108.6 + 9,5 mm Hg) and decreased LVEDP (MI: 6.37 ± 0.9 mmHgx MI Soybean: 4.72 ± 0.4 mm Hg). In addition, the inotropic response to extracellular Ca+ 2 was also significantly increased in the treated groups compared to non-treated. Conclusion: This study demonstrated that treatment with soybean oil intramuscular for 15 days prevented the decrease in cardiac performance in rats that suffered myocardial infarction without modifying the area of the scar.